Levanon [videorecording (DVD)] = Lebanon - Maoz, Samuel. 1962-; Maoz, Samuel. 1962-; Donat, Yoav; Moshonov, Michael; Tiran, Itay; Cohen, Oshri, 1984- ([distributed by] Sony Pictures Home Entertainment, 2011)
In 1982, during the First Lebanon War, a tank manned by a novice crew of Israeli soldiers is led into a town previously bombed by the air force. The situation spins out of control, testing the mental toughness of the men inside a confined space with only the lens of a periscopic gun sight to see the madness outside.